The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/cncr.22340
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome for metastatic papillary renal cell carcinoma patients

Abstract: BACKGROUND. Most clinical trial reports in metastatic renal cell carcinoma (RCC) do not distinguish between histologic subtypes, making it difficult to assess specific treatment efficacy. The current retrospective study sought to define clinical features and outcome data for metastatic papillary RCC. METHODS. Clinical features, treatment outcome, and survival were evaluated in 38 patients with metastatic papillary RCC who underwent clinical evaluation at Memorial Sloan‐Kettering Cancer Center (MSKCC) between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 44 publications
(47 reference statements)
0
60
0
Order By: Relevance
“…43 PRCC is less aggressive than CCRCC with metastases reported in 5% to 12% of patients. 19,44 In recent years, PRCC has been divided into 2 subtypes on the basis of cytoplasmic features, nuclear features, and the presence or absence of nuclear pseudostratification. 45 A 2005 study 46 suggested that PRCC can be further subdivided into 4 different morphologic categories, which correspond to 2 different molecular groups, based on gene expression profiling data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43 PRCC is less aggressive than CCRCC with metastases reported in 5% to 12% of patients. 19,44 In recent years, PRCC has been divided into 2 subtypes on the basis of cytoplasmic features, nuclear features, and the presence or absence of nuclear pseudostratification. 45 A 2005 study 46 suggested that PRCC can be further subdivided into 4 different morphologic categories, which correspond to 2 different molecular groups, based on gene expression profiling data.…”
mentioning
confidence: 99%
“…59 These genetic differences likely underlie the decreased response to sunitinib and other targeted therapies seen in cases of metastatic PRCC. 11,44 There was hope that the study of cases of inherited type 1 PRCC, which are due to activating germline mutations of the c-MET oncogene, might provide insight into the inner workings of sporadic PRCC. Unfortunately, these activating mutations are uncommon outside of the syndromic setting, being present in approximately 10% of sporadic type 1 PRCCs.…”
mentioning
confidence: 99%
“…5 However, patients with advanced stage unresectable papillary RCC have similar prognoses to those with clear cell RCC with a reported median survival of 8 to 13 months. 6,7 The largest series reporting on 270 patients with papillary RCC demonstrated that about 4% of patients presented with metastatic disease, with lung (47% to 78%) and retroperitoneal lymph nodes (34% to 61%) as the two most common sites of metastasis. 6,7 Treatment has included surgery or chemotherapy alone, or a combination of the two depending on both patient and tumor related factors, such as the site of metastasis and patient performance status.…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib (sunitinib malate; SU11248; SUTENT ® ; Pfizer Inc, New York, NY, USA) is a novel multitargeted tyrosine kinase inhibitor with high binding affinity for VEGFR and PDGFR that recently has shown anti-tumor and anti-angiogenic activities [49] . This drug recently received approval from the US Food and Drug Administration (FDA) for two applications: advanced gastrointestinal stromal tumors (GISTs) [50] and renal cell carcinoma [51] , in patients who are resistant or intolerant to treatment with Imatinib. Since the Tie receptor is an RTK, Sunitinib may be suitable to down-regulate the activity of the angiopoietin pathway.…”
Section: Discussionmentioning
confidence: 99%